HUBUNGAN PEMBERIAN ASI EKSLUSIF DENGAN KEJADIAN STUNTING PADA BALITA DI BLUD UPTD PUSKESMAS LANGENSARI 1 KOTA BANJAR - Supriyatun; Yuliana Windi; Deuis Nurdiawati (Poltekkes Kemenkes Tasikmalaya, 2024)
ABSTRACT Background: Children who are stunted are more vulnerable to infectious infections and may experience chronic malnutrition, which can impede their physical and mental development. One of the risk factors for childhood stunting is inadequate nutrition for toddlers, particularly breast-feeding, which is the best source of nutrients for babies. According to preliminary study data from January to April 2023 at BLUD UPTD Puskesmas Langensari 1, the prevalence rate of stunting is 146 children under five. Additionally, the data on exclusive breastfeeding coverage for the same period shows that 127 children under five receive exclusive breast milk, while 50 toddlers do not receive exclusive breast milk. Purpose: The purpose of this research is to examine the association between toddler stunting incidence and exclusive breastfeeding at the BLUD UPTD Langensari 1 Health Center in Banjar City. Method: A cross-sectional study design is employed together with correlational or association research. Data from 1,995 toddlers in BLUD UPTD Puskesmas Langensari 1 Banjar City between January and April of 2023 comprise the population for this study, with a sample size of 95. Random sample was the sample method employed. Result: The analysis's p-value of 0.001 indicates a strong correlation between the incidence of stunting in toddlers at the BLUD UPTD Langensari 1 Health Center in Banjar City and exclusive breastfeeding.